A Hybrid Mock Circulation for Control Algorithms of Ventricular Assist Devices - Salesch Tobias; Gesenhues Jonas; Abel Dirk (Current Directions in Biomedical Engineering, 2019)
This paper deals with the design, simulation and control of a new lightweight hybrid Mock-Loop (MCL) concept. The proof of concept is evaluated by two simulation approaches. First, the design parameters are chosen by an optimal control problem. Second, a cascading controller structure is evaluated in a simulation. Both show that with a suitable range of the design parameter the new lightweight concept can be used as a MCL. To validate these findings, further investigations with the MCL under realistic test conditions are required.